2014
DOI: 10.1519/jsc.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Responses to Outdoor vs. Laboratory Cycling

Abstract: The purpose of this study was to determine the physiological and psychological responses to laboratory vs. outdoor cycling. Twelve recreationally trained male cyclists participated in an initial descriptive testing session and 2 experimental trials consisting of 1 laboratory and 1 outdoor session, in a randomized order. Participants were given a standardized statement instructing them to give the same perceived effort for both the laboratory and outdoor 40-km trials. Variables measured include power output, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 16 publications
3
41
2
1
Order By: Relevance
“…The samples in these acute trials comprised of university students ( n = 10 studies), university students and staff ( n = 2), recreational or competitive athletes ( n = 5), healthy adults ( n = 5), postmenopausal women ( n = 2), patients post-stroke ( n = 1), and primary school kids ( n = 1). Most acute studies ( n = 16) consisted of both male and female participants (mean % female vs. male: 55% vs. 45%), whereas four trials each comprised of female- [43,44,45,46] and male-only samples [14,47,48,49]—one trial [50] did not report participants gender.…”
Section: Resultsmentioning
confidence: 99%
“…The samples in these acute trials comprised of university students ( n = 10 studies), university students and staff ( n = 2), recreational or competitive athletes ( n = 5), healthy adults ( n = 5), postmenopausal women ( n = 2), patients post-stroke ( n = 1), and primary school kids ( n = 1). Most acute studies ( n = 16) consisted of both male and female participants (mean % female vs. male: 55% vs. 45%), whereas four trials each comprised of female- [43,44,45,46] and male-only samples [14,47,48,49]—one trial [50] did not report participants gender.…”
Section: Resultsmentioning
confidence: 99%
“…Other effects [20,29,30,32,115,131,137,138] described economic impacts, contributions to rural economy, cost-effectiveness, or philosophical statements such as sport for development and peace or “worldmaking”.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to explain the time differential between the Rollers and Trainers, recently, Mieras and associates (7) concluded that cyclists training indoors and/or lab settings should work at a higher perceived exertion, hence, intensity to acquire similar benefits similar to that of training outdoors to ultimately transcend the participant’s efforts into the field, namely, performance. Interestingly enough, within the current study, both groups, Rollers and Trainers, worked at the same relative intensity (i.e., % HRmax) throughout the 8 weeks, yet still displayed marked differences in 10-km TT performance improvements.…”
Section: Discussionmentioning
confidence: 99%